Peningkatan Minat Belajar Sejarah Indonesia Menggunakan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Pada Peserta Didik Kelas X9 SMAN 3 Medan - Febriani, Meli (ALACRITY : Journal of Education, 2024)
This research aims to increase students' interest in learning using the Teams Games Tournament type cooperative learning model in class X9 students at SMAN 3 Medan for the 2023/2024 academic year. The learning interest referred to in this research is measuring students' active participation both physically and mentally. This type of research is Classroom Action Research (PTK), where the teacher is the implementer of the learning while the researcher is the observer. This research design uses the Kemmis and Mc model. Taggart. This research was carried out in the even semester of the 2023/2024 academic year, namely in March. The research subjects were class X9 students at SMAN 3 Medan, consisting of 36 students. The object of research is students' learning interest. Data collection techniques use observation and interviews. Data were analyzed descriptively and presented in the form of tables and graphs. The research results showed an increase in students' learning activeness, namely in cycle I it was 71.64% (good category), then in cycle II it increased to 83.42% (very good category). This means an increase of 11.78%. Thus, the use of the Teams Games Tournament type cooperative learning model in the Indonesian History subject can increase the learning interest of class X9 students at SMAN 3 Medan.